Antecedents And Outcomes Of Internet Abuse In The Workplace : The Moderating Effects Of Gender, Age And Experience - Yulihasri, . (2012)
Internet abuse is a problem that encountered by almost all of the organizations nowadays as Internet becomes one of the fundamental facilities in the organizations. The impacts of Internet abuse on employees and organizations can be tremendous if the problem were left to be unsolved. Hence, a study in the Eastern and developing countries like Malaysia is needed. Furthermore, there is a need for a theoretical framework that can provide more sophisticated and holistic investigation on the Internet abuse problem. Therefore, the purpose of this study is to empirically investigate the antecedents and outcomes of Internet abuse behaviour at the workplace. The research framework in this study is an integration of Decomposed Theory of Planned Behaviour (DTPB) and Outcomes of Deviant Use of Internet Technology (DUIT). By drawing theoretical support from DTPB, there are three antecedents of Internet abuse behaviour, namely attitude, subjective norm, and perceived behaviour control. The DUIT model conceptualized the outcomes of Internet abuse as work inefficiency, Internet security threats, loneliness, and depression. Moreover, the framework examined the roles of demographics particularly gender, age and Internet experience as moderators between the three antecedent variables and Internet abuse behaviour. A total of 501 usable responses collected from fulltime employees based on purposive sampling were used for the purpose of this study. The findings of this study indicated that Internet abuse level in Malaysia was slightly higher than moderate, which deserved proper attention before it goes rampant.